Kolaborasi Multi Stakeholders Dalam Praktik Corporate Social Responsibility Pada Konservasi Terumbu Karang di Tanjung Kupang - Wisnu Eka Baskhara; Rois Amsari; Raihan Akbar Khalil; Panji Aditya Priatna (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
As a company active in the field of oil fuel distribution, PT Pertamina Patra Niaga Fuel Terminal Tenau has implemented the Corporate Social Responsibility (CSR) program, namely the conservation of coral reefs in the area of Tanjung Kupang, Kelurahan Alak through the Kelompok Anana Laut, under the name of Lembu Lestari. The programme is important to note, because it is unique in its multi-stakeholder cohesion that has played an active and collaborative role in the success of the programme, given that in 2021, Tropical Cyclone Seroja destroyed 90% of the coral reefs in Tanjung Kupang and its surroundings, causing damage to the biodiversity that lives in the area. The research uses qualitative-descriptive methods combined with CSR implementation theory and multi-stakeholder collaboration. The research data is obtained through two stages, observation and focus group discussion. The results of the research showed that the role of multi stakeholders involved in the Lembu Lestari program carried out by PT Pertamina Patra Niaga Fuel Terminal Tenau understood the important role of stakeholder in supporting the company's operations, which is also correlated with the Regional Medium-Term Development Plan (RPJMD), by managing the relationship with the stakeholder, the company also refers to the established principles of governance. Nevertheless, this activity also has its own challenges, namely, how to pursue consistency of stakeholder engagement, as well as identify the next steps to ensure that the Lembu Lestari program is sustainable.